Terahertz optical measurements of correlated motions with possible allosteric function - Niessen, Katherine A.; Xu, Mengyang; Markelz, A. G. (Biophysical Reviews, 2015)
A suggested mechanism for allosteric response is the distortion of the energy landscape with agonist binding changing the protein structure's access to functional configurations. Intramolecular vibrations are indicative of the energy landscape and may have trajectories that enable functional conformational change. Here, we discuss the development of an optical method to measure the intramolecular vibrations in proteins, namely, crystal anisotropy terahertz microscopy, and the various approaches which can be used to identify the spectral data with specific structural motions.